Analisis Penerapan SAK EMKM Pada Usaha Kecil Menengah Kecamatan Mulyorejo - Oktabilla Timoriawan, Shanella; Suhartini, Dwi (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in contributing to Gross Domestic Product (GDP) of 61% or Rp9,580 trillion. In obtaining access to capital, MSME owners are required to prepare financial reports that can provide financial information for decision making on KUR provision. IAI and the Financial Accounting Standards Board issued a standard to facilitate the preparation of MSME financial reports, namely SAK EMKM, which came into effect on January 1, 2018. In reality, in the field, most MSME owners in Indonesia have not made records according to SAK EMKM. The data analysis technique uses a qualitative descriptive method. The results of the study were 90% of MSMEs did not know SAK EMKM and 10% knew SAK EMKM, but did not know the contents of SAK EMKM. As many as 20% of MSMEs have made financial records in the form of order books and cash books and 80% have not made business financial records. The obstacles that have a big influence on making financial records are the lack of knowledge and business owners who think that the process of making financial reports is complicated and takes a lot of time. Because many MSMEs do not know SAK EMKM and have not made records, it is hoped that MSMEs will realize the importance of financial records and increase their understanding of SAK EMKM by attending training from the local government or learning independently.